Episteme Dakwatologi Komunikasi: Menakar Komunikasi Islam dalam Epsitemologi Triangular Relationship - Wahyudin, Aep (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
Building a paradigm on Islamic communication does not actually have to start from the scratch. Synthesis heavy foundation can be use the existing communication theories, but the more important for Muslim scholars is to create a new synthesis through meta-theories aspects which include epistemology, ontology and perspectives. Settling on the aspects of the value and ethics dimensions must be able to collaborate with monotheism and responsibilities hereafter. Islamic communication functions is to realize the meaning of the equation, thus there will be changes in attitude or behavior of the Muslim societies. While the ultimate goal of Islam is the point which stressed on the aspect communicant, not the communicator. In the aspect of social change and community development, communication tends to be positivistic and functionally oriented to the individual, instead the social system and sociocultural functions that are critical to stimulate social changes. Quality of communication regarding the values of truth, simplicity, kindness, honesty, integrity, fairness, validity of the message and sources, are the important aspect in the IslamicÂ communication. Therefore, in this perspective, communication is established to joint Islamic Triangular Relationship between